Buyers' Enduring Involvement With Online Auctions: A New Zealand Perspective - Abdul-Ghani, Eathar Mohammad (Auckland University of Technology, 2009)
Consumer-to-consumer (C2C) online auctions represent an important new marketplace from which consumers can access the goods they require, an alternative marketplace to bricks-and-mortar and online retail stores. Sellers are often ordinary consumers and the items on sale are often second-hand household items, although, modern C2C auction sites also accommodate small businesses selling unused products. Consumer behaviour in online C2C auctions is unlike consumer behaviour in bricks-and-mortar or online retail stores. While considerable research has been conducted into the dynamics of bidding in online C2C auctions little research has addressed the motives for consumers’ ongoing participation in this marketplace. The concept of consumer involvement may explain the amount of time and money consumers are spending in online C2C auctions and the frequency of their visits to auction sites. In the context of this thesis, involvement is defined as the long-term and enduring relevance, connection and relatedness of online auctions to a consumer’s life. The aim of this research is to explore the ways in which the consumer involvement construct offers an explanation for variation in buyers’ ongoing use of online auctions. The thesis also seeks to discover which consumer motives contribute to buyers’ enduring involvement with online auctions. TradeMe is New Zealand’s most popular online C2C auction site. In a country of just four million people, the TradeMe auction site has more than 2 million members and accounts for more than 50 per cent of Internet traffic originating from New Zealand websites. This study of buyers who use the TradeMe auction site, offers the opportunity to study online auction consumers in this unique context. Based on an extensive literature review, eighteen propositions were developed regarding buyer motives for enduring involvement with online C2C auctions. In-depth, semi-structured interviews were conducted with twenty TradeMe users, to test these propositions and to identify any further motives for enduring involvement with auctions that had not been revealed in the literature review. Interviews were audio-recorded and transcribed in full. NVivo8 qualitative data analysis software was used to code the interview transcripts. Thematic analysis reveals six themes representing buyer motives for enduring involvement with online auctions. The significant contribution of this thesis is to identify involvement as a useful construct for explaining consumer behaviour in online auctions. In addition to utilitarian and hedonic motives for involvement with online auctions, the interviews reveal that the buyers have a number of social and personal motives for involvement with online auctions. Analysis of the qualitative dataset also reveals a set of marketer activities which encourage ongoing use of the auction site, and a number of factors (anti-motives) which discourage use of the auction site. The research reveals the existence of an off-line community of auction users who value the social contact they experience with one another outside the auction site. Ongoing buyer-seller relationships are also shown to develop outside the auction site, prompted by an initial auction transaction. TradeMe users often express loyalty to the TradeMe website because they are proud of its New Zealand origins, feel secure in using a local auction website, believe they are supporting small New Zealand businesses by buying from TradeMe, and believe they are practicing sustainable consumption behaviour by purchasing second-hand goods. Future research should develop a multi-item, quantitative measure of buyers’ enduring involvement with online auctions and test the validity of this measure with further empirical data.
Keywords: Online auctions; Consumer involvement; Consumer motives; Business relationships; TradeMe